Integration of linkage and physical genome map of oil palm for the exploration of important traits within palm species - Ong, Ai Ling (2022)
Perennial crops, such as oil palm (Elaeis guineensis Jacq.) have a long breeding cycle (typically 20 years per cycle) and inherently heterogeneous populations. Oil palm is the most productive and traded vegetable oil globally compared to other oil crops such as soybean, rapeseed etc, but it has only undergone four generations of selection since breeding started 80 years ago. No doubt genome-enabled biology in oil palm breeding is crucial yet genetics and crop improvement have been actively pursued in research but with limited deployment in the industry. Further, the oil yield has stagnated for many years, hence the realistic approach of genome-based breeding is needed.